Riflessioni sulla formazione dello psicoterapeuta - Anzilotti, Carlo (Il sogno della farfalla, 2019)
The aim of this article is to open a debate on the future of psychotherapeutic training, after the end of the Analisi Collettiva held by Massimo Fagioli. In this original form of group psychotherapy, the training was linked to cure and research, a collective process that cannot be repeated in any other context. It is therefore necessary to propose a discussion among psychotherapists. This would address two fundamental issues: one’s own personal elaboration of the experience had and the investigation of new approaches in order to offer a valuable training to future generations. Working groups composed by psychotherapists with a variety of backgrounds could provide fellow trainees with valuable input to practise psychotherapy in an original form. Furthermore, the article highlights the responsibility borne by psychiatrists and psychotherapists who trained in the Analisi Collettiva. This does not relate only to the professional sphere but also to the ability of transmitting one’s own professional training and knowledge to colleagues who did not have the opportunity to take part in Fagioli’s seminars.